Activation of the Complement System in the Lower Genital Tract During Pregnancy and Delivery - Livson, Sivan; Jarva, Hanna; Kalliala, Ilkka; Lokki, A. Inkeri; Heikkinen-Eloranta, Jenni; Nieminen, Pekka; Meri, Seppo (Frontiers in Immunology, 2021)
Background Human pregnancy alters profoundly the immune system. The local involvement and mechanisms of activation of the complement system in the cervicovaginal milieu during pregnancy and delivery remain unexplored. Objectives To determine whether normal pregnancy and delivery are associated with local activation of complement or changes in the immunoglobulin profile in the cervix. Study Design This study was designed to assess IgA, IgG, and complement activation in the cervicovaginal area in three groups of patients: i) 49 pregnant women (week 41+3–42+0) not in active labor, ii) 24 women in active labor (38+4–42+2), and iii) a control group of nonpregnant women (n=23) at child-bearing age. We collected mucosal samples from the lateral fornix of the vagina and external cervix during routine visits and delivery. The Western blot technique was used to detect complement C3 and its activation products. For semiquantitative analysis, the bands of the electrophoresed proteins in gels were digitized on a flatbed photo scanner and analyzed. IgA and IgG were analyzed by Western blotting and quantified by ELISA. One-way ANOVA and Tukey’s Multiple Comparison tests were used for statistical comparisons. Results A higher abundance but lower activation level of C3 in both the external cervix (P<0.001) and lateral fornix of the vagina (P<0.001) was observed during delivery (58 ± 22, n= 24) in comparison to the groups of nonpregnant (72 ± 13%; mean ± SD, n=23) and pregnant women (78 ± 22%, n=49). Complement activating IgG was detected in higher abundance than IgA in the cervicovaginal secretions of pregnant women. In a small proportion samples also C3-IgG complexes were detected. Conclusions Our results reveal an unexpectedly strong activation of the complement system and the presence IgG immunoglobulins in the cervicovaginal area during pregnancy, active labor, and among nonpregnant women. In contrast to the higher amounts of C3 in the cervicovaginal secretions during labor, its activation level was lower. Complement activating IgG was detected in higher concentrations than IgA in the mucosal secretions during pregnancy and labor. Taken together our results imply the presence a locally operating humoral immune system in the cervicovaginal mucosa.